Recent Advances of Light-Mediated Theranostics - Ai, Xiangzhao (2016)
Currently, precision theranostics have been extensively demanded for the effective treatment of various human diseases. Currently, efficient therapy at the targeted disease areas still remains challenging since most available drug molecules lack of selectivity to the pathological sites. Among different approaches, light-mediated therapeutic strategy has recently emerged as a promising and powerful tool to precisely control the activation of therapeutic reagents and imaging probes in vitro and in vivo, mostly attributed to its unique properties including minimally invasive capability and highly spatiotemporal resolution. Although it has achieved initial success, the conventional strategies for light-mediated theranostics are mostly based on the light with short wavelength (e.g., UV or visible light), which may usually suffer from several undesired drawbacks, such as limited tissue penetration depth, unavoidable light absorption/scattering and potential phototoxicity to healthy tissues, etc. Therefore, a near-infrared (NIR) light-mediated approach on the basis of long-wavelength light (700-1000 nm) irradiation, which displays deep-tissue penetration, minimized photo-damage and low autofluoresence in living systems, has been proposed as an inspiring alternative for precisely phototherapeutic applications in the last decades. Despite numerous NIR light-responsive molecules have been currently proposed for clinical applications, several inherent drawbacks, such as troublesome synthetic procedures, low water solubility and limited accumulation abilities in targeted areas, heavily restrict their applications in deep-tissue therapeutic and imaging studies. Thanks to the amazing properties of several nanomaterials with large extinction coefficient in the NIR region, the construction of NIR light responsive nanoplatforms with multifunctions have become promising approaches for deep-seated diseases diagnosis and therapy. In this review, we summarized various light-triggered theranostic strategies and introduced their great advances in biomedical applications in recent years. Moreover, some other promising light-assisted techniques, such as photoacoustic and Cerenkov radiation, were also systemically discussed. Finally, the potential challenges and future perspectives for light-mediated deep-tissue diagnosis and therapeutics were proposed.